2009
DOI: 10.1021/cm901320p
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Organic Solar Cells Based on Planar Metallophthalocyanines

Abstract: Organic solar cells based on planar metallophthalocyanines (MPc, M = Cu, Zn, Pd, Pc)/3,4,9,10-perylene tetracarboxylic bisbenzimidazole (PTCBI) were investigated. PdPc/PTCBI solar cells have a peak external quantum efficiency of 30.9%, which is almost twice as those of conventional solar cells based on CuPc and ZnPc/PTCBI. Optical modeling was carried out using a transfer matrix algorithm in order to determine the exciton diffusion lengths for four MPcs. External quantum efficiency measurement and optical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 26 publications
5
73
0
Order By: Relevance
“…In 2001, Forrest and Peumans fabricated bilayer heterojunction OPVs based on CuPc and C 60 with a PCE of 3.6% under 150 mW cm −2 simulated AM1.5G illumination. [47] SubPc/C 60 OPVs exhibited much higher V OC (0.97 V) as compared to CuPc/C 60 -based devices, resulting in an enhancement of PCE from 0.9 to 2.1%. [71] By systematically tuning energy level, a bilayer OPV based on subnaphthalocyanine chloride (SubNc) donor and hexachlorinated SubPc (Cl 6 -SubPc-Cl) acceptor achieved a PCE as high as 6.86% and a V OC of 1.04 V. [70] The optimized bilayer device based on MC dye ID583/C 60 showed PCE up to 3.9% with a high FF of 0.70.…”
Section: Bilayer Structurementioning
confidence: 97%
See 1 more Smart Citation
“…In 2001, Forrest and Peumans fabricated bilayer heterojunction OPVs based on CuPc and C 60 with a PCE of 3.6% under 150 mW cm −2 simulated AM1.5G illumination. [47] SubPc/C 60 OPVs exhibited much higher V OC (0.97 V) as compared to CuPc/C 60 -based devices, resulting in an enhancement of PCE from 0.9 to 2.1%. [71] By systematically tuning energy level, a bilayer OPV based on subnaphthalocyanine chloride (SubNc) donor and hexachlorinated SubPc (Cl 6 -SubPc-Cl) acceptor achieved a PCE as high as 6.86% and a V OC of 1.04 V. [70] The optimized bilayer device based on MC dye ID583/C 60 showed PCE up to 3.9% with a high FF of 0.70.…”
Section: Bilayer Structurementioning
confidence: 97%
“…[22] The mixed interlayer was recognized as the first bulk heterojunction layer in small molecule-based OPVs. In 1992, Sariciftci et al demonstrated that photoexcitation of a mixture of a conjugated polymer and fullerene (C 60 ) resulted in an ultrafast, highly efficient photoinduced electron transfer. [23] In 1995, Heeger et al created the bulk heterojunction (BHJ) concept, which refers to a blend of bicontinuous and interpenetrating donor and acceptor components in a bulk volume.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been applied in prototypes of solar cells [1][2][3][4]. Furthermore, it is already known that phthalocyanines (including ZnPc) can exist in multiple types of crystalline phases [5]; in particular, the metastable -ZnPc (higher electrical conductivity) and the stable -ZnPc (lower electrical conductivity) [6] need to be distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that replacement of centered metal ions with palladium in widely used planar metallophthalocyanines ͑MPcs͒ such as CuPc and ZnPc resulted in a longer exciton diffusion length. 6 In this article, we report the enhancement of PCE in p-i-n type solar cells of ZnPc and C 60 by substituting palladium phthalocyaine ͑PdPc͒ for the ZnPc p-layer. In addition, charge carrier collection efficiency in mixed layers of MPc and C 60 is also discussed.…”
mentioning
confidence: 99%
“…This stems from a longer exciton diffusion length in PdPc ͑ϳ10 nm͒ compared to ZnPc ͑ϳ6 nm͒. 6 Insertion of a mixed i-layer of ZnPc: C 60 leads to enhancement in PCE ͑A-and C-type cells͒. The PCE increases with increasing thickness of the mixed layer up to 20 nm.…”
mentioning
confidence: 99%